(Des)caminhos da militarização no Brasil: Programa Nacional das Escolas Cívico-Militares - Nunes, Fabiana Boschetti (Universidade Federal de São Carlos, 2025)
The National Program of Civic-Military Schools (PECIM), implemented between 2019 and 2022 in the context of Brazilian public education, is configured as the process of militarization of public education at the national level. The investigation stems from the researcher's experience as the director of a school involved in the process of joining the program in the municipality of Sorocaba (SP), marked by mobilizations of the school community, civil society and judicial decisions, but mainly due to the scarcity of studies on the subject. Given the above, the objective is to critically analyze the PECIM guideline in light of the educational principles that underpin public education. To carry out such analyses, a qualitative approach is adopted, and the following data collection sources are used: bibliographic review, bibliographic and documentary research, as well as documentary analysis, outlined by Discursive Textual Analysis (DTA). The study is organized into six chapters, which present: the conceptualization of the terms "military" and "militarization," including in the educational field; historically contextualize management models based on military principles; and investigate the normative and regulatory documents that guide the functioning of the program. Next, the theoretical framework is outlined, based on critical authors such as Freire, Adorno, Saviani, Giroux, Apple, and Libâneo, on the constitutionality of Brazilian education, and the conceptions of the analytical categories—dialogue and democracy—that emerged during the writing of this research are presented. Finally, critical analyses of the program's guidelines are developed, highlighting the program's (mis)steps in relation to educational principles, from the perspective of (anti)dialogicity and (anti)democracy. The conclusion of this work demonstrates that PECIM is an educational model based on the logic of discipline, vertical hierarchy, and control, which contradicts the educational principles that govern Brazilian public education. Although repealed in 2023, PECIM continues to influence state and municipal initiatives, which reinforces the relevance of analytical studies and ongoing debates about the direction of Brazilian public schools.
(Mis)directions of militarization in Brazil: National Program of Civic-Military Schools
Keywords: Programa Nacional das Escolas Cívico-Militares; National Program of Civic-Military Schools; Militarização da Educação Pública Brasileira; Princípios educacionais; Diálogo e democracia; Militarization of Brazilian Public Education; Educational principles; Dialogue and democracy; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade